Orbital paraganglioma in a dog - Fischer, Maria-Christine; Taeymans, Olivier N.; Monti, Paola; Scurrell, Emma J.; Eddicks, Lina; Matiasek, Kaspar; Busse, Claudia (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
A 10-year-old Rottweiler presented with right-sided moderately painful exophthalmia, blindness, absence of dazzle and pupillary light reflexes, a swollen optic nerve head and ventrolateral indentation of the globe. On magnetic resonance imaging, a 3 x 2 x 2 cm mass with a fluid filled center and contrast-enhancing periphery was noted posteriolateral of the globe. Orbital ultrasound was used for a guided fine needle aspirate of the mass. Cytology revealed moderate numbers of polygonal cells with lightly basophilic cytoplasm. Several cells showed nuclear pseudoinclusions. Histopathology following exenteration of the orbit revealed an infiltrative, extradural neoplasm surrounding the optic nerve. Cells were arranged in packets. Neoplastic cells were immunopositive for neuron specific enolase, synaptophysin and chromogranin A and immunonegative for cytokeratin. Findings were consistent with an extra-adrenal paraganglioma (neuroendocrine tumour). Although complete excision could not be confirmed on histopathology, the owners reported no apparent tumour recurrence 25 months after surgery. In conclusion a paraganglioma should be considered as a differential diagnosis of an orbital mass.
Keywords: Canine; neuroendocrine tumour; extra-adrenal paraganglioma; retrobulbar; orbit; immunohistochemistry